Leukoreductive response to the combination of sorafenib and chemotherapy in hyperleukocytosis of FLT3-ITD mutated pediatric AML - Schmidt, Franziska; Erlacher, Miriam; Niemeyer, Charlotte; Reinhardt, Dirk; Klusmann, Jan-Henning (Frontiers in Pediatrics, 2022)
Twelve to 22% of pediatric acute myeloid leukemia (AML) patients present with hyperleukocytosis, which is one of the main risk factors of early death due to its clinical complications: leukostasis, causing pulmonary or central nervous system injuries, tumor lysis syndrome, and disseminated intravascular coagulation. Sorafenib is a multi-kinase inhibitor that blocks the Fms-Related Tyrosine Kinase 3 receptor (FLT3) in AML patients with a FLT3-internal tandem duplication (FLT3-ITD), leading to a reduction of proliferation. Here we report four de novo diagnosed or relapsed pediatric FLT3-ITD–positive AML patients with hyperleukocytosis, which were treated with sorafenib in combination with cytoreductive chemotherapy prior to the start of the induction phase. We observed a fast reduction of white blood cells in peripheral blood and bone marrow. This resulted in a rapid clinical stabilization of the patients. Adverse side effects—such as dermatologic toxicity, elevation of transaminases and hypertension—occurred but were mild and inductive chemotherapy could be started in parallel or subsequently. This implies sorafenib as a safe and effective treatment option in combination with chemotherapy during cytoreductive prephase for children with this life-threatening condition.